Is the calcium antagonist debate having an effect on clinical practice? - Hobbs, R (1997)
The controversies over the long-term safety of calcium antagonists have produced considerable debate in bath the medical and lay press. However, there are no data on whether this debate has influenced routine clinical practice. As most drugs in the Western healthcare systems are prescribed by primary care physicians, the aim of this study was to explore the perceptions of primary care clinicians with regard to their prescribing of calcium antagonists. Semistructured interviews of primary care physicians were performed in four countries, the Netherlands, Germany, Spain, and the United States. These interviews investigated the levels of awareness of primary care physicians about the recent calcium antagonist debate, and whether the debate had influenced their personal prescribing practice. Physicians were also asked if they considered the duration of calcium antagonist action to be clinically important. The results indicated that, despite the recent controversy over the safety of calcium antagonists, primary care physicians were largely unaware of the debate and had made no significant alterations to their routine practice. Although 15% cited potential nonspecified side effects, only 14% recalled a specific connection between the use of calcium antagonists and adverse cardiac events or higher mortality. Knowledge of adverse risks was significantly greater among physicians in the United States than among physicians in the other 3 countries. Finally, 90% of respondents were aware of the differences in duration of action of various calcium antagonists; of these, 90% felt that this had clinical significance.